Flight detection of Caliroa cerasi L. (Hymenoptera: Tenthtedinidae) adults en the Andean Reigon of Parallel 42, Argentina - Mareggiani, G.=700 1 Bartoloni, N.; Gorosito, N.; Laffaye, C.
(Es, En)
Ilus., 20 ref.
Keywords: PRUNUS AVIUN; PLAGAS DE PLANTAS; INSECTA; HYMENOPTERA; INSECTOS DEPREDADORES DE LAS HOJAS; ARGENTINA; CEREZO